Blockchain-Based Local Energy Market Enabling P2P Trading: An Australian Collated Case Study on Energy Users, Retailers and Utilities - Liaqat Ali; M. Imran Azim; Jan Peters; Vivek Bhandari; Anand Menon; Vinod Tiwari; Jemma Green; S. M. Muyeen (IEEE Access)
This paper presents a collated case study on local energy market (LEM) in Australia, in which energy users take part frequently in peer-to-peer (P2P) energy trading among themselves considering the agile presence of energy retailers and distribution utilities. To do so, first, an overview is provided in regard to LEM architecture, trading model with energy retailers, and the blockchain structure. Then, a new P2P trading mechanism is proposed in the LEM that enables both energy users, i.e., sellers and buyers, to reap financial benefits compared to the existing business-as-usual (BAU) model — where local power is exported and imported via feed-in-tariff (FiT) and time-of-use (ToU) rates. The proposed LEM framework also exploits residential battery energy storage systems (RBESSs); and the community battery energy storage systems (CBESSs) to balance local supply and demand appropriately and contributes towards lowering exports/imports from/to power grids by means of bilateral P2P transactions while the inclusion of responsible energy retailers are assured. Moreover, the margins of both energy retailers and distribution utilities are kept unchanged or increased to some extent by the proposed trading model to incorporate them in the LEM framework effectively. Finally, diverse case studies are provided to validate the proposed LEM mechanism with various studied models and demonstrate the superior performance in contrast with the present-day BAU model.